Optimization of hot press forging parameters in direct recycling of aluminium chip (AA 6061) - Lajis, Mohd Amri; Khamis, Siti Salwa; Yusuf, Nur Kamilah (Trans Tech Publications, 2014)
This study introduces a new approach of direct recycling using the hot press forging process that eliminates the two intermediate processes of cold-compact and pre-heating. This method leads to low energy consumption without intervening the metallurgical processes. In this study, the optimum of machined chips from high speed milling is recycled by hot press forging. The mechanical properties and surface integrity of the different chips were investigated. The performance of recycled aluminium AA 6061 chips in the mechanical and physical properties were compared with the original aluminium billet. Response surface methodology (RSM) was used to develop mathematical model of the effects on pre-compaction cycle, holding time and suitable pressure significant to the process. It is hoped that, utilization of primary metal could be fully utilized by direct recycling technique (hot press forging) introduced in this study and at the same time developing a sustainable manufacturing process technology for future needs.